Reaching, benefitting, empowering, and transforming: AICCRA gender and social inclusion interventions moving the needle - Ewell, Hanna Louise Deborah; Moore, Maya (2025)
The working paper describes a survey conducted with gender focal points that identifies gender-relevant innovations and maps these to the reach, benefit, empower, transform framework (RBET). All 33 reached and benefitted women, 20 advanced agricultural empowerment, 15 economic, 10 social and 7 political. Only three were deemed transformative. This shows AICCRA interventions are moving the needle from reach to empowerment, with transformation nascent but promising. Sustained, context-specific strategies coupling material gains with norm change, linking innovation to policy, and monitoring shifts in agency and institutional reform—not participation alone—are needed to deliver climate-resilient agri-food systems at scale.